UJARAN KEBENCIAN PADA AKUN TWITTER AMANO PIKAMEE - Maguna Eliastuti; Muhammad Azhar; Analisa Fitria; Endang Mintarsih; Sarkiah Hafsari; Merina Fitriyani (Yayasan Nusantara Hasana Berdikari, 2023)
Hate speech is a phenomenon that has existed for a long time, but with the rapid development of technology, this has also become a driving factor for hate speech cases, especially on social media Twitter after it was acquired by Elon Musk. The type of research used is descriptive qualitative which aims to provide a description of the types of implicatures in tweets and comments related to Pikamee uploads. The data in this study are in the form of comments and tweets containing hate speech directed at via Twitter accounts. The data source used is in the form of screenshots that can no longer be accessed or traced via a Twitter account. Data collection techniques are obtained from the results of observation and analysis to prove the content of hate speech. The results of the study show that there are four forms of implicature in the form of: (1) Condemnation, (2) Resentment, (3) Schadenfreude, (4) Threats.